Indian Fairy Tales - Jacobs, Joseph. 1854-1916; Batten, John Dickson, 1860-1932 (New York : Dover Publications, 1969)
Twenty-nine traditional tales from India include "The Tiger, the Brahman, and the Jackal," "The Lion and the Crane," and "Why the Fish Laughed."
Reprint of the 1892 ed.
"Notes and references": p. [227]-255.
Keywords: Fairy tales -- India; Fairy tales; Folklore -- India